The Internal Structure of Mercury's Core Inferred From Magnetic Observations. Issue 12 (27th December 2021) - Wardinski, I.; Amit, H.; Langlais, B.; Thébault, E.
Abstract: Previous models of Mercury's core magnetic field based on high altitude data from first MESSENGER flybys revealed an axisymmetric structure of the field. Here, we use low altitude MESSENGER data covering the entire mission period to construct spherical harmonic models based on various spatial norms. Although we find a dominantly axisymmetric field, our models nevertheless include detectable deviations from axisymmetry. These non‐axisymmetric features appear at high latitudes, resembling intense geomagnetic flux patches at Earth's core‐mantle boundary. Based on this core field morphology, we then attempt to infer Mercury's internal structure. More specifically, assuming that Mercury's high‐latitude non‐axisymmetric features are concentrated by downwellings at the edge of the planet's inner core tangent cylinder, and accounting for the presence of a stably stratified layer at the top of Mercury's core, we establish a relation between the inner core size and the thickness of the stratified layer. Considering plausible ranges, we propose that Mercury's inner core size is about 500–660 km, which corresponds to a stratified layer thickness of 880–500 km, respectively. Plain Language Summary: Measurements of the magnetic field of Mercury taken by the MESSENGER space probe allow us to construct a model of the magnetic field generated inside Mercury. This internal field is generated within the core of Mercury by a magnetic dynamo process. This field is highly symmetric with respect to the axis of rotation, but very much weaker than Earth's magnetic field. Deviations from the axisymmetry of the field allow us to infer the internal structure of Mercury's core. A combined interpretation of Mercury's gravity field observations and our results provide a certain range for Mercury's inner core size, which is likely to be solid. We also infer the size of Mercury's dynamo and the thickness of the stratified layer above the dynamo region. We find that Mercury's inner core size is about 500–660 km, which corresponds to a stratified layer thickness of 880–500 km, respectively. The size of the dynamo region is between 680 and 900 km. This study provides new insights to the internal structure of a planet's core that are inferred from observations of its magnetic field. Key Points: We model Mercury's internal magnetic field from MESSENGER data with spherical harmonics Our core field model contains non‐axisymmetric features from which we make inferences of Mercury's internal structure We estimate Mercury's inner core radius of ∼500–660 km and a corresponding thickness of a top stratified layer of ∼880–500 km